Transformation of Local Cultural Values Through Islamic Education: An Ethnographic Study of the Indigenous Community of Kasepuhan Gelar Alam, Sukabumi Regency - Yayan Supian; Jaja Jahari; Setia Gumilar; Dewi Sadiah (PT Publikasiku Academic Solution, 2025)
This research explores the transformation of local cultural values through Islamic education within the indigenous community of Kasepuhan Gelar Alam, Sukabumi Regency, West Java. Amidst globalization and modernization, local wisdom traditions such as gotong royong (mutual cooperation), musyawarah (deliberation), and sopan santun (courtesy) face erosion. Nevertheless, this community has successfully preserved these values by integrating them harmoniously with Islamic teachings for more than seven centuries. Employing an ethnographic qualitative approach, this study gathered data through participant observation, in-depth interviews, and documentation involving traditional leaders, religious figures, and local residents. The analysis was conducted inductively, exploring meanings, processes, and sociocultural interactions in daily life. The results show that the transformation of local cultural values occurs through the integration of Islamic teachings into communal practices and informal education. Traditional and religious leaders act as the main agents in transmitting and contextualizing these values. Supporting factors include the congruence between Islamic and customary values and community awareness, while challenges arise from generational gaps, limited formal education, and conservative resistance. The impact is the emergence of a distinctive form of local Islamic identity, religious behavior rooted in cultural ethics, and youth participation in sustaining ancestral traditions. This study highlights the strategic role of Islamic education in cultural preservation and moral formation in indigenous communities